2022
DOI: 10.3389/fphar.2022.941182
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing thiopurine therapy in children with acute lymphoblastic leukemia: A promising “MINT” sequencing strategy and therapeutic “DNA-TG” monitoring

Abstract: Thiopurines, including thioguanine (TG), 6-mercaptopurine (6-MP), and azathioprine (AZA), are extensively used in clinical practice in children with acute lymphoblastic leukemia (ALL) and inflammatory bowel diseases. However, the common adverse effects caused by myelosuppression and hepatotoxicity limit their application. Metabolizing enzymes such as thiopurine S-methyltransferase (TPMT), nudix hydrolase 15 (NUDT15), inosine triphosphate pyrophosphohydrolase (ITPA), and drug transporters like multidrug resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 98 publications
0
3
0
Order By: Relevance
“…Clinical PGx testing in children is strongly supported by evidence in some areas, such as TPMT testing in association with thiopurine therapy for childhood leukemia [21][22][23][24][25] , CYP3A5 testing in association with tacrolimus therapy for childhood refractory nephrotic syndrome [12,26] . However, research results showed that there was still room for expansion and development in the variety of PGx testing conducted in China (Figure 7).…”
Section: Increase the Variety Of Gtpm Tests And Expand The Scope Of C...mentioning
confidence: 99%
“…Clinical PGx testing in children is strongly supported by evidence in some areas, such as TPMT testing in association with thiopurine therapy for childhood leukemia [21][22][23][24][25] , CYP3A5 testing in association with tacrolimus therapy for childhood refractory nephrotic syndrome [12,26] . However, research results showed that there was still room for expansion and development in the variety of PGx testing conducted in China (Figure 7).…”
Section: Increase the Variety Of Gtpm Tests And Expand The Scope Of C...mentioning
confidence: 99%
“…Thiopurine drugs, azathioprine, 6-mercaptopurine, and 6-thioguanine, are widely used to treat cancer, onco-hematological diseases, and autoimmune diseases and to prevent transplant rejection [63]. TPMT, together with nudix hydrolase, is the most im-portant enzyme for thiopurine metabolism [64], and TPMT activity is inversely correlated with the levels of the active metabolites, as observed in children with leukemia [65] and in patients with inflammatory bowel diseases [66]. Patients with high TPMT activity are at risk of poor treatment efficacy due to a low production of active metabolites.…”
Section: Polymorphisms Of the Most Important Phase II Metabolism Enzymesmentioning
confidence: 99%
“…Similarly, genetic variants in ITPA were associated with neutropenic fever in the same population and XDH rs2281547 was identified as a genetic risk factor for then grade 4 hematologic toxicities. Arguably, when using 6-MP, it is important to take into account genetic polymorphisms in enzymes other than TPMT and NUDT15 that are involved in its pathway ( Guo et al, 2022 ). This consideration might help prevent the occurrence of hematological toxicities.…”
Section: Overview Of Contributionsmentioning
confidence: 99%